2003
DOI: 10.1002/pen.10079
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilizers based on polypropylene grafted with itaconic acid derivatives. Effect on polypropylene/polyethylene terephthalate blends

Abstract: New types of compatibilizers based on functionalized polypropylene (PP) were synthesized by radical melt grafting either with monomethyl itaconate or dimethyl itaconate. The effect of these new modified PP compounds were tested as compatibilizers in PP/polyethylene terephthalate (PET) blends. Blends with compositions 15/85 and 30/70 by weight of PP and PET were prepared in a single‐screw extruder. Morphology of the compatibilized blends revealed a very fine and uniform dispersion of the PP phase as compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…14,22,26 Within these later studies, compatibilization could be achieved after the addition of a small amount of epoxy to the PP/PBT/poly(propylene-gmaleic anhydride) (PP-MAH) system. 26 Other compatibilizers found to be used in polyolefin/polyester systems include PP grafted with phenol formaldehyde, 29 isocyanate 30 and itaconate groups, 31 liquid-crystalline ionomers and polymers, 32,33 epoxidized ethylene propylene diene rubber, 34 and bismaleimide 35 and silane 36 molecules. These publications reported the existence of specific interactions between those materials and PET or PBT that caused some level of blend compatibilization.…”
Section: Introductionmentioning
confidence: 99%
“…14,22,26 Within these later studies, compatibilization could be achieved after the addition of a small amount of epoxy to the PP/PBT/poly(propylene-gmaleic anhydride) (PP-MAH) system. 26 Other compatibilizers found to be used in polyolefin/polyester systems include PP grafted with phenol formaldehyde, 29 isocyanate 30 and itaconate groups, 31 liquid-crystalline ionomers and polymers, 32,33 epoxidized ethylene propylene diene rubber, 34 and bismaleimide 35 and silane 36 molecules. These publications reported the existence of specific interactions between those materials and PET or PBT that caused some level of blend compatibilization.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding itaconic acid, this organic compound has been used as compatibilizer for blends of thermoplastic polymers [23,24]. Yazdani-Pedram et al [23] used PP functionalized with itaconic acid as compatibilizer in blends of PP/PET. They found that the presence of modified PP improves the tensile mechanical properties of PP/PET blends.…”
mentioning
confidence: 99%
“…56 Dimethyl itaconate as compatibilizer derived agent exhibits only a small activity to increase the impact resistance of PET in PP/PET blend.…”
Section: Poly(propylene)mentioning
confidence: 99%